REGAIN STUDY: Retrospective Study to Assess the Effectiveness, Tolerability, and Safety of Ferric Carboxymaltose in the Management of Iron Deficiency Anemia in Pregnant Women - Saleema Wani; Mariyam Noushad; Shabana Ashiq (Anemia)
Iron deficiency anemia (IDA) during pregnancy arises because of preexisting inadequate stores or complex physiological changes and can lead to serious maternal and fetal complications. Oral iron, either as iron sulfate or fumarate, with or without folic acid, is the most commonly used treatment for IDA in pregnancy. Intravenous (IV) iron has a role in the treatment of IDA in pregnancy, particularly in women who present late, display severe anemia (Hb ≤ 9 g/dL), or risk factors, and are intolerant/noncompliant of oral iron. Previously, administration of IV iron was minimal, owing to potentially serious anaphylactic reactions. Recently, new IV iron products have been developed, offering better compliance, tolerability, efficacy, and a good safety profile. Our study aimed to assess the effectiveness, safety, and tolerability of IV ferric carboxymaltose (FCM) in the treatment of IDA in pregnant women in the UAE. Data from 1001 pregnant women who received at least one administration of FCM (500, 1000, or 1500 mg) during their second or third trimester of pregnancy (2 years backward from study initiation) were collected retrospectively from electronic medical records at Corniche Hospital, Abu Dhabi, UAE. Results showed that 41.4% of the women were able to achieve an increase of ≥2 g/dL in blood hemoglobin overall. A change of ≥2 g/dL was achieved by 27.5% of women administered a dose of 500 mg, 39.2% of women administered a dose of 1000 mg, and 63.9% of women administered a dose of 1500 mg of IV FCM. This indicates a directly proportional relationship between increasing IV FCM dose and the increase of ≥2 g/dL in blood hemoglobin. A total of 7 (0.7%) women reported mild, nonserious adverse events during the study. Within the limits of this retrospective study, IV FCM therapy was safe and effective in increasing the mean hemoglobin of pregnant women with IDA.